1990
DOI: 10.1111/j.1432-1033.1990.tb15622.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and functional properties of cobra (Naja naja naja) venom Kunitz‐type trypsin inhibitor

Abstract: A trypsin inhibitor from the venom of the cobra Nuja nuju nuja has been isolated by a single step of reversephase high-performance liquid chromatography. The protein strongly inhibits trypsin (Ki = 3.5 pM). The primary structure was determined by peptide analysis of the [ ''C]carboxymethylated inhibitor. The 57-residue polypeptide chain belongs to the family of Kunitz-type inhibitors, and exhibits 42% residue identity with bovine pancreatic trypsin inhibitor. The structure shows only 70% identity with the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…Jim Hesson of AcademicEnglishSolutions.com revised the English. Andreev et al, 2008, Appel et al, 2008, Bode et al, 1993, Burke and Dennis, 2009, de la Vega et al, 1998, Guo et al, 2005, Han et al, 2005, Harrison and Bonning, 2010, Hooper, 1994, Krishnan et al, 1994, Kramer et al, 1993, Markland, 1998, Millers et al, 2009, Ortiz et al, 2013, Rjeibi et al, 2011, Roberts et al, 2006, Scott et al, 1990, Shafqat et al, 1990, Silva et al, 2009, Tan et al, 2006, Valdez-Cruz et al, 2007, Valentin and Lambeau, 2000, Yamazaki and Morita, 2004, You et al, 2009, Zhang et al, 2011 …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Jim Hesson of AcademicEnglishSolutions.com revised the English. Andreev et al, 2008, Appel et al, 2008, Bode et al, 1993, Burke and Dennis, 2009, de la Vega et al, 1998, Guo et al, 2005, Han et al, 2005, Harrison and Bonning, 2010, Hooper, 1994, Krishnan et al, 1994, Kramer et al, 1993, Markland, 1998, Millers et al, 2009, Ortiz et al, 2013, Rjeibi et al, 2011, Roberts et al, 2006, Scott et al, 1990, Shafqat et al, 1990, Silva et al, 2009, Tan et al, 2006, Valdez-Cruz et al, 2007, Valentin and Lambeau, 2000, Yamazaki and Morita, 2004, You et al, 2009, Zhang et al, 2011 …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Study of the distribution of proteinase inhibitor in snake venom has shown their presence in H. heamachatus, N. nivea and N. haje venom [113]. Later on the Kunitz-type inhibitors were isolated from the venoms of H. heamachatus and N. nivea [114], N. naja [115,116], O. hannah [117] as well as N. atra [118]. All these proteins share homology with bovine pancreatic trypsin inhibitor.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…They act as competitive antagonists binding to, and inhibiting, the active site of serine proteases such as trypsin and chymotrypsin [3]. Kunitz-type inhibitors have been isolated from the venom of a number of Elapidae and Viperidae snakes [4][5][6][7]. In addition to their ability to act as protease inhibitors, some snake venom kunitz-like homologs have evolved as neurotoxins by inhibiting calcium and potassium channels [8].…”
Section: Introductionmentioning
confidence: 99%